Cracks Detection Using Active Modal Damping and Piezoelectric Components - B. Chomette; A. Fernandes; J.-J. Sinou (Shock and Vibration)
The dynamics of a system and its safety can be considerably affected by the presence of cracks. Health monitoring strategies attract so a great deal of interest from industry. Cracks detection methods based on modal parameters variation are particularly efficient in the case of large cracks but are difficult to implement in the case of small cracks due to measurement difficulties in the case of small parameters variation. Therefore the present study proposes a new method to detect small cracks based on active modal damping and piezoelectric components. This method uses the active damping variation identificated with the Rational Fraction Polynomial algorithm as an indicator of cracks detection. The efficiency of the proposed method is demonstrated through numerical simulations corresponding to different crack depth and locations in the case of a finite element model of a clamped-clamped beam including four piezoelectric transducers.